Papel de vias de reconhecimento inato na resistência frente a infecção oral por Neospora caninum em camundongos - França, Flávia Batista Ferreira (2019)
Neospora caninum is an obligate intracellular parasite with worldwide distribution that causes abortions in cattle and billionaire losses in livestock. The investigation of immune response against this infection usually adopts parenteral infection in murine models. However, it is essential to understand the immune mechanisms after oral infection wich accurately mimics natural condition. Th1 adaptative immune response is crucial to protect against this intracellular protozoan, wich is mainly regulated by IFN-γ production. Thus, in this work, we aimed to evaluate the immune response triggered by N. caninum oral infection in mice, focusing in the IFN- γ production induced by innate pathway TLR-MyD88 and inflamassome. For this purpose, we used C57BL/6 mice orally infected with tachyzoites after neutralization of the gastric pH. We analyzed the survival, tissue lesions, cytokine production, and specific antibody production in infected mice. We observed that WT mice infected by oral route presented higher levels of serum specific IgG, composed mainly by IgG2 antibodies. DNA of the parasite was detected mainly in the distal jejunum and ileum, however, no histological alterations were detected through the gut. Meanwhile, acute inflammatory lesions were observed in livers and lungs of orally infected mice, related with the presence, in situ, of parasite DNA and IFN-γ production. In order to analyze the role of these key cytokine, we infected IFN-γ genetically deficient mice with N. caninum tachyzoites by gavage. We observed that IFN γ-/- mice presented reduced signs of morbidity during the beginning of infection. However, after six days of infection, IFN γ-/- mice succumbed quickly the infection, with no signs of inflammatory lesions in analyzed tissues. After this results, we investigated the pathway responsible to IFN-γ production during oral infection using MyD88-/- and Caspase-1/11-/- mice infected with N. caninum. A significant reduction in the IFN-γ production in Caspase-1/11-/- mice was observed in this experiment, whereas MyD88 deficient mice did not present alterations in the levels of this cytokine. These findings are supported by histological analyses that demonstrated a reduction of lung and liver tissue lesions in Caspase-1/11-/- mice, similar to the result previously observed in the absence of IFN-γ. In conclusion, this work demonstrated the quick passage of the N. caninum protozoa into the small intestine of mice, and then injuring abdominal and thoracic organs through replicative and inflammatory processes mediated by IFN-γ. Also, this cytokine is induced by the activation of the inflamassome complex. Overall, we can get the possibility to enhance the control of pathogenicity induced by N. caninum infection.